2021
DOI: 10.1073/pnas.2104099118
|View full text |Cite
|
Sign up to set email alerts
|

A functional mammalian display screen identifies rare antibodies that stimulate NK cell–mediated cytotoxicity

Abstract: Therapies that boost the antitumor immune response have shown a great deal of success. Although most of these therapies have focused on enhancing T cell functions, there is a growing interest in developing therapies that can target other immune cell subsets. Like T cells, natural killer (NK) cells are cytotoxic effector cells that play a key role in the antitumor response. To advance the development of NK-based therapies, we developed a functional screen to rapidly identify antibodies that can activate NK cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Although most immune therapies have focused on enhancing T cell functions, there is a growing interest in developing therapies that can target other immune cell subsets, such as natural killer cells. For example, one study focusing on a functional screen to rapidly identify antibodies that can activate NK cells, found that bispecific antibodies targeting NCR3 can potently activate NK cells (28). In terms of studies focused on the NK cell phenotype in RCC, researchers have investigated the phenotype of NK cells extracted from peripheral blood lymphocytes and TILs in renal cancer patients, as early as 1997 (29).…”
Section: Discussionmentioning
confidence: 99%
“…Although most immune therapies have focused on enhancing T cell functions, there is a growing interest in developing therapies that can target other immune cell subsets, such as natural killer cells. For example, one study focusing on a functional screen to rapidly identify antibodies that can activate NK cells, found that bispecific antibodies targeting NCR3 can potently activate NK cells (28). In terms of studies focused on the NK cell phenotype in RCC, researchers have investigated the phenotype of NK cells extracted from peripheral blood lymphocytes and TILs in renal cancer patients, as early as 1997 (29).…”
Section: Discussionmentioning
confidence: 99%
“…Performing massively parallel genetic assays ( 1–3 ) and directed evolution ( 4 , 5 ) in mammalian cells offers unique opportunities that other systems cannot provide. Besides supporting proper protein folding, posttranslational modifications and subcellular localization, the mammalian system has been ingeniously applied for engineering proteins possessing special functions of biomedical interests, including stem cell differentiation ( 6 , 7 ), virus maturation inhibition ( 8 ), NK cell stimulation ( 9 ), tolerance to lysosomal pH ( 10 ) and receptor activation or blockage ( 11–14 ). In addition, mammalian cells have been utilized to generate novel ion channels ( 15 , 16 ), GPCRs ( 17 ), enhanced pluripotency factors ( 18 ) and functional TCRs, CARs and T cell antigens ( 19–21 ).…”
Section: Introductionmentioning
confidence: 99%